International Arbitration and International Public Policy. Genesis, Issue and ‘Conflittualistica’ Theory - Zappalá, Francesco (2023)
The principle of the autonomy of the contract will in the choice of procedure law is an axiom in international trade disputes. Nevertheless, in several legal systems there are restrictions to this principle residing in the public policy. It is possible to identify the principles of public policy such as those that inspire a particular jurisdiction and are an echo of the fundamentals values of a society. The concept responds to a general idea of the supremacy of society over individuals. Public policy is a mechanism by which the State represses special agreements that may pose a threat to its essential interests and political relations. The methodology used is documentary. .